New GIS tools support natural gas distribution - HECHT, L (Pipeline & gas journal, 1996)
Northwest Natural Gas, a Portland, OR, distribution company changed to a geographic information system (GIS) in place of its first-generation computer-aided drafting system to automate more of its high-level functions and spread technology throughout the company. With GIS, the usual drawings now look better, and data are provided behind the graphics, incorporating pipeline characteristics, material types, and base map information. The company's engineers also have begun using the GIS software's maps and computer programming features to automate or enhance certain company functions such as leakage and corrosion inspections, work-order management and emergency response. Additionally, they are successfully using the GIS as a tool for gas network modeling and analysis.